Pa'belle Fishermen Empowerment: A Communicative Action Perspective in An Industrialized Society - Ismail, Ince Rahma; Idris, Rabihatun; Kesuma, Andi Ima (Tamaddun Life, 2023)
This research examines the empowerment process of Pa'belle fishermen from a communicative action perspective, recognizing that all their activities serve as communication tools with meaning and messages for others. The study aims to analyze the problems faced by the fishermen during the empowerment process, as well as the communicative actions they undertake and the direction of their empowerment. The research utilizes a qualitative Single Case Study approach, with 15 purposively selected fishermen as informants who have at least two years of experience working as fishermen and understand the challenges experienced by fishermen and fishermen groups. Data collection involved in-depth interviews, participant observation, and literature study, while data analysis employed a three-step technique of data categorization, data reduction, and conclusion drawing. The study findings revealed various problems faced by Pa'belle fishermen in the empowerment process, including challenges with government support such as DAU 2021 assistance, the need for "Balean" wooden stakes, nets, extension workers' limited understanding of fishermen's socio-cultural realities, and exclusive participation in meetings with village heads. Internal problems within fishermen groups were also identified, such as the lottery-based determination of Sero numbers, inadequate information dissemination from extension workers to group members, lack of coordination among members, and a group leader who is not open or independent. The study also identified the communicative actions of Pabelle' fishermen during the empowerment process. These actions included intense communication, providing self-managed assistance tailored to the fishermen's needs, active participation in every activity, conveying ideas intensively, daring to express criticism and input on occurring problems, displaying a critical perspective on illegal logging issues, as well as exhibiting power, access, and control over their resources. In terms of the direction of Pabelle' fishermen empowerment, the study suggests the need to strengthen the role of fishermen groups, the digitalization of fishermen's activities, increased environmental awareness, and the involvement of external parties outside the government. This research demonstrates that empowerment processes among the Pa'belle fishermen involve various communicative actions that convey their social situations to others. The findings highlight the key problems encountered by the fishermen, the communicative actions they undertake during the empowerment process, and the directions for further empowerment initiatives. These insights contribute to a better understanding of the empowerment process and offer guidance for policymakers and practitioners seeking to empower marginalized fishing communities.